When Do Governments Support Common Goods for Health? Four Cases on Surveillance, Traffic Congestion, Road Safety, and Air Pollution - Jesse B. Bump; Sumithra Krishnamurthy Reddiar; Agnès Soucat (Taylor & Francis Group, 2019)
Common goods such as air, water, climate, and other resources shared by all humanity are under increasing pressure from growing population and advancing globalization of the world economy. Safeguarding these resources is generally considered a government responsibility, as common goods are vulnerable to market failure. However, governments do not always fulfill this role, and face many challenges in doing so. This observation-that governments only sometimes address common goods problems-informs the central question of this paper: when do governments act in support of common goods? We structure our inquiry using a framework derived from three theories of agenda setting, emphasizing problem perception, the role of actors and collective action patterns, strategies and policies, and catalyzing circumstances. We used a poll of experts to identify important common goods for health: disease surveillance, environmental protection, and accountability. We then chose four historical cases for analysis: the establishment of the Epidemic Intelligence Service in the US, transport planning in London, road safety in Argentina, and air quality control in urban India. Our analysis of the collective evidence of these cases suggests that decisions to advance government action on common goods require a concisely articulated problem, a well-defined strategy for addressing the problem, and leadership backed by at least a few important groups willing to cooperate. Our cases reveal a variety of collective action patterns, suggesting that there are many routes to success. We consider that the timing of an intervention in support of common goods depends on favorable circumstances, which can include a catalyzing event but does not necessarily require one.